Aircrew personality and the impact of crew resource management training on hazardous attitudes : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Freeman, Carolyn (Massey University, 2005)
It has been established that poor non-technical skills, such as crew communication and coordination, in aircrew, are antecedents to accidents and incidents in aviation. Crew Resource Management (CRM) training has developed over the last 20 years in response to the need to educate crews in resource management, decision-making, situational awareness and other human factors related topics. This current study sought to evaluate the CRM training currently administered by the Royal New Zealand Air Force (RNZAF). Evaluation was made on three of Kirkpatrick's levels; reaction, learning and behaviour. Personality as a mediator in the relationship of CRM attitudes to behaviour was also investigated. Finally personality differences in the sample were identified. Results showed that the RNZAF CRM training was perceived by aircrew as useful and 100% of trainees felt this training should be offered to all aircrew. At the learning level of evaluation the results revealed a positive attitude change in one scale of the Cockpit Management Attitudes Questionnaire - 'Recognition of Stressors'. The personality trait Agreeableness was found to mediate the relationship between attitudes and behaviour post CRM training. Agreeableness and Conscientiousness also explained 25% of the variance in scores of CRM behaviours. Finally it was established that pilots display higher levels of Instrumentality and lower levels of Neuroticism than non-pilot aircrew. Officers display higher levels of Extroversion and lower levels of Expressivity than Non Commissioned Officers. The results are discussed in terms of their implication for future RNZAF research and training. Limitations of the current study and areas for future research are presented.
Keywords: New Zealand; Royal New Zealand Air Force -- Officers; Flight crews; Training of -- Evaluation; Aeronautics, Military -- Human factors; Aeronautics, Military -- Safety measures